6.3 KiB
Executable file
Taylor polynomials
Linearization
A function f(x)
about x = a
may be linearized into
P_1(x) = f(a) + f'(a)(x-a),
obtaining a polynomial that matches the value and derivative of f
at x = a
.
Taylor's theorem
Even better approximations of f(x)
can be obtained by using higher degree polynomials if f^{n+1}(t)
exists for all t
in an interval containing a
and x
. Thereby matching more derivatives at x = a
,
P_n(x) = f(a) + f'(a)(x-a) + \frac{f''(a)}{2!}(x-a)^2+ ... + \frac{f^{(n)}(a)}{n!}(x-a)^n.
Then the error E_n(x) = f(x) - P_n(x)
in the approximation f(x) \approx P_n(x)
is given by
E_n(a) = \frac{f^{(n+1)}(s)}{(n+1)!}(x-a)^{n+1},
where s
is some number between a
and x
. The resulting formula
f(x) = f(a) + f'(a)(x-a) + \frac{f''(a)}{2!}(x-a)^2 + ... + \frac{f^{(n)}(a)}{n!}(x-a)^n + \frac{f^{(n+1)}(s)}{(n+1)!}(x-a)^{n+1},
for some s
between a
and x
, is called Taylor's formula with Lagrange remainder; the Lagrange is the error term E_n(x)
.
Proof:
Observe that the case n=0
of Taylor's formula, namely
f(x) = P_0(x) + E_0(x) = f(a) + \frac{f'(s)}{1!}(x-a),
is just the Mean-value theorem for some s
between a
and x
\frac{f(x) - f(a)}{x-a} = f'(s).
Using induction to prove for n > 0
. Suppose n = k-1
where k \geq 1
is an integer, then
E_{k-1}(x) = \frac{f^{(k)}(s)}{k!}(x-a)^k,
where s
is some number between a
and x
. Consider the next higher case: n=k
. Applying the Generalized Mean-value theorem to the functions E_k(t)
and (t-a)^{k+1}
on [a,x]
. Since E_k(a)=0
, a number u
in (a,x)
is obtained such that
\frac{E_k(x) - E_k(a)}{(x-a^{k+1}) - (a-a)^{k+1}}= \frac{E_k(x)}{(x-a)^{k+1}} = \frac{E_k'(u)}{(k+1)(u - a)^k}.
Since
\begin{array}{ll}
E_k'(u)&=\frac{d}{dx}(f(x)-f(a)-f'(a)(x-a)-\frac{f''(a)}{2!}(t-a)^2-...-\frac{f^{(k)}(a)}{k!}(t-a)^k)|_{x=u} \
&= f'(u) - f'(a) - f''(a)(u-a)-...-\frac{f^{(k)}(a)}{(k-1)!}(u-a)^{k-1}
\end{array}
is just E_{k-1}(u)
for the function f'
instead of f
. By the induction assumption it is equal to
\frac{(f')^{(k)}(s)}{k!}(u-a)^k = \frac{f^{(k+1)}(s)}{k!}(u-a)^k
for some s
between a
and u
. Therefore,
E_k(x) = \frac{f^{(k+1)}(s)}{(k+1)!}(x-a)^{k+1}
Big-O notation
f(x) = O(u(x))
for x \to a
if and only if there exists a k > 0
such that
|f(x)| \leq k|u(x)|
For all x
in the open interval around x=a
.
The following properties follow from the definition:
- If
f(x) = O(u(x))
asx \to a
, thenCf(x) = O(u(x))
asx \to a
for any value of the constantC
. - If
f(x) = O(u(x))
asx \to a
andg(x) = O(u(x))
asx \to a
, thenf(x) \pm g(x) = O(u(x))
asx \to a
. - If
f(x) = O((x-a)^ku(x))
asx \to a
, then\frac{f(x)}{(x-a)^k} = O(u(x))
asx \to a
for any constantk
.
If f(x) = Q_n(x) + O((x-a)^{n+1})
as x \to a
, where Q_n
is a polynomial of degree at most n
, then Q_n(x) = P_n(x)
.
Proof: Follows from the properties of the big-O notation
Let P_n
be the Taylor polynomial, then properties 1 and 2 of big-O imply
that R_n(x) = Q_n(x) - P_n(x) = O((x - a)^{n+1})
as x \to a
. It must be shown that R_n(x)
is identically zero so that Q_n(x) = P_n(x)
for all x
. R_n(x)
may be written in the form
R_n(x) = c_0 + c_1(x-a) + c_2(x-a)^2 + ... + c_n(x-a)^n
If R_n(x)
is not identically zero, then there is a smallest coefficient c_k
k \leq n
, such that c_k \neq 0
, but c_j = 0
for 0 \leq j \leq k -1
R_n(x) = (x-a)^k(c_k + c_{k+1}(x-a) + ... + c_n(x-a)^{n-k}).
Therefore,
\lim_{x \to a} \frac{R_n(x)}{(x-a)^k} = c_k \neq 0.
However, by property 3
\frac{R_n(x)}{(x-a)^k} = O((x-a)^{n+1-k}).
Since n+1-k > 0
, \frac{R_n(x)}{(x-a)^k} \to 0
as x \to a
. This contradiction shows that R_n(x)
must be
identically zero.
Maclaurin formulas
Some Maclaurin formulas with errors in big-O notation. These may be used in constructing Taylor polynomials from compsite functions. As x \to 0
-
\frac{1}{1-x} = 1 + x + ... + x^n + O(x^{n+1}),
-
\ln(1+x) = x - \frac{x^2}{2} + \frac{x^3}{3} - ... + (-1)^{n-1}\frac{x^n}{n} + O(x^{n+1}),
-
e^x = 1 + x + \frac{x^2}{2!} + ... + \frac{x^n}{n!} + O(x^{n+1}),
-
\sin x = x - \frac{x^3}{3!} + \frac{x^5}{5!} - ... + (-1)^n\frac{x^{2n+1}}{(2n+1)!} + O(x^{2n+3}),
-
\cos x = 1 - \frac{x^2}{2!} + \frac{x^4}{4!} - ... + (-1)^n\frac{x^{2n}}{(2n)!} + O(x^{2n+1}),
-
\arctan x = x - \frac{x^3}{3} + \frac{x^5}{5} - ... + (-1)^n\frac{x^{2n+1}}{2n+1} + O(x^{2n+3}).
Example
Construct P_4(x)
for f(x) = e^{\sin x}
around x=0
.
e^{\sin x} \approx 1 + (x - \frac{x^3}{3!} + \frac{x^5}{5!}) + \frac{1}{2!}(x - \frac{x^3}{3!} + \frac{x^5}{5!})^2 + \frac{1}{3!}(x - \frac{x^3}{3!} + \frac{x^5}{5!})^3
\begin{array}{ll}
P_4(x) &= 1 + x \frac{1}{2}x^2 + (-\frac{1}{6} + \frac{1}{6})x^3 + (-\frac{1}{6} + \frac{1}{4!})x^4 + O(x^5), \
&= 1 + x \frac{1}{2}x^2 - \frac{1}{8}x^4 + O(x^5).
\end{array}
Evaluating limits with Taylor polynomials
Taylor and Macluarin polynomials provide a method for evaluating limits of indeterminate forms.
Example
Determine the limit \lim_{x \to 0} \frac{x \arctan x - \ln(1+x^2)}{x \sin x - x^2}
.
\begin{array}{ll}
x \sin x - x^2 \approx x^2 - \frac{x^4}{6} + O(x^6) - x^2 = - \frac{x^4}{6} + O(x^6) \
x \arctan x - \ln(1+x^2) \approx x^2 - \frac{x^4}{3} + O(x^6) - x^2 + \frac{x^4}{2} + O(x^6) = \frac{x^4}{6} + O(x^6)
\end{array}
\lim_{x \to 0} \frac{\frac{x^4}{6} + O(x^6)}{- \frac{x^4}{6} + O(x^6)} = -1
L'Hostpital's rule
Suppose the function f
and g
are differentiable on the interval (a,b)
, and g'(x) \neq 0
there. Also suppose that \lim_{x \downarrow a} f(x) = \lim_{x \downarrow a} g(x) = 0
then
\lim_{x \downarrow a} \frac{f(x)}{g(x)} = \lim_{x \downarrow a} \frac{f'(x)}{g'(x)} = L.
The outcome is exactly the same as using Taylor polynomials.
Proof: using Taylor polynomials around x = a
.
\lim_{x \to a} \frac{f(x)}{g(x)} = \lim_{x \to a} \frac{f(a) + f'(a)(x - a) + \frac{f''(a)}{2}(x-a)^2 + O((x-a)^3)}{g(a) + g'(a)(x-a) + \frac{g''(a)}{2}(x-a)^2 + O((x-a)^3)}.
If f(a)
and g(a)
are both zero
\lim_{x \to a} \frac{f'(a)(x - a) + \frac{f''(a)}{2}(x-a)^2 + O((x-a)^3)}{g'(a)(x-a) + \frac{g''(a)}{2}(x-a)^2 + O((x-a)^3)},
enzovoort.